Trend of Reference Crop Evapotranspiration and its Correlation with Climatic Parameters in Khulna and Rajshahi Districts of Bangladesh - Acharjee, TK; Ullah, M Shariot; Sojib, KH; Hasan, MS (Journal of Environmental Science and Natural Resources, 2022)
Reference crop evapotranspiration (ETO) is an important hydro-meteorological phenomenon, which is influenced by changing climate. This study estimated the trends ETO and identified the correlation of changes in ETO with climatic parameters in Khulna and Rajshahi districts of Bangladesh. Daily observed climatic parameters of thirty years (1984– 2013) were used in CropWat model to estimate changes in monthly and seasonal ETO. Trend analysis of ETO and climatic parameters were done by Mann-Kendall test and Sen’s slope estimation. Correlation between ETO and climatic parameters were analyzed. The results showed a decreasing trend of ETO over most of the period of the year in Khulna and Rajshahi districts. On monthly basis estimation, decreasing trends of relative humidity, wind speed and sun shine hours in Khulna district, and decreasing trends of wind speed and sun shine hours in Rajshahi district played the dominant roles for the decreasing rate of ETO under recent climate change. On seasonal basis estimation, decreasing trends of relative humidity, wind speed and sun shine hours in Khulna district, and decreasing trends of wind speed and sun shine hours in Rajshahi district played the dominant roles for the decreasing rate of ETO under changing climatic condition. Changes in ETO were most strongly correlated with sun shine hours and most weakly with minimum temperature for both Khulna and Rajshahi. Wind speed was most strongly correlated with ETO for Dry/Rabi season. The findings of this study would be useful for agricultural water management of Bangladesh. Environ. Sci. & Natural Resources, 13(1&2): 1-12, 2020